2014 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2014
DOI: 10.1109/icassp.2014.6855098
|View full text |Cite
|
Sign up to set email alerts
|

Accent rating by native and non-native listeners

Abstract: This study investigates the influence of listener native language with respect to talker native language on perception of degree of foreign accent in English. Listeners from native English, Finnish, German and Mandarin backgrounds rated the accentedness of native English, Finnish, German and Mandarin talkers producing a controlled set of English sentences. Results indicate that non-native listeners, like native listeners, are able to classify non-native talkers as foreign-accented, and native talkers as unacce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…For instance, non-native teachers rated fluency lower than did the native raters (Gilquin et al 2016;Rose 2017). Some studies also showed that native speakers seemed to be more tolerant than non-native speakers when judging accent (Koster and Koet 1993;Wester and Mayo 2014). Winke et al (2012) also found that raters whose L2 is the test takers' L1 tended to be lenient in scoring.…”
Section: Assessing Spoken Learner English Using Cefrmentioning
confidence: 99%
“…For instance, non-native teachers rated fluency lower than did the native raters (Gilquin et al 2016;Rose 2017). Some studies also showed that native speakers seemed to be more tolerant than non-native speakers when judging accent (Koster and Koet 1993;Wester and Mayo 2014). Winke et al (2012) also found that raters whose L2 is the test takers' L1 tended to be lenient in scoring.…”
Section: Assessing Spoken Learner English Using Cefrmentioning
confidence: 99%
“…The study consists of English speech from native and non-native speakers. We used the same three English utterances used in [15,16,23] spoken by all the speakers for which subjective accentedness ratings are available.…”
Section: Speakersmentioning
confidence: 99%
“…It may well be that these judges are biased against nonstandard speakers, not only when they listen to their native language speech but also when listening to their target language speech, in which they recognize features of the non-standard language. Indeed, some non-native speaker judges are unable to identify native speakers (Wester & Mayo 2014; anecdotally, we have personally experienced situations where teachers of English who were native speakers of Dutch did not recognize native speakers of English amongst their students, often because these students were speakers of a non-standard variety of English, e.g. from the Windward Islands).…”
Section: Introductionmentioning
confidence: 99%